Membangun Kinerja Pegawai Dilingkungan Kantor Dinas Pendidikan Kota Salatiga: Studi Tentang Pengaruh Budaya Organisasi dan Tunjangan Tambahan Penghasilan Terhadap Kinerja Yang Dimediasi Motivasi Kerja - Tri Maryani; Samtono Samtono (Universitas 45 Surabaya, 2025)
The aim of the research here is to analyze and explain the influence of organizational culture, additional income allowances on work motivation, analyze and explain organizational culture, additional income allowances, and motivation on employee performance, as well as whether work motivation mediates organizational culture and additional income on the performance of service employees. Salatiga City education.The research approach here is a quantitative approach to the type of causality. As for the sampling technique, the census technique was used, meaning that all members of the population were appointed as samples, while the total number of subjects who were appointed as samples were 85 subjects, while the data collection technique used questionnaire techniques with 5 option Likert scale measurements, while data analysis was done using multiple regression analysis, as well as tests. Mediation/path analysis is used to determine the direct or indirect influence of the independent variable on the dependent variable.The results of the research obtained the following results: 1. There is a positive and significant influence of organizational culture on work motivation. 2. There is a positive influence of additional income allowance on work motivation, but it is not significant. 3. There is a positive and significant influence of organizational culture on employee performance. 4. There is a positive influence of additional income allowance on employee performance but it is not significant. 5. There is a positive and significant influence of work motivation on employee performance. 6. Work motivation does not mediate organizational culture on employee performance. 7. Work motivation does not mediate additional income benefits on employee performance.